The Effect of Tik Tok Live Streaming in Increasing Consumer Trust and Purchasing Decisions - Elvi Susanti; Suhroji Adha (Formosa Journal of Applied Sciences, 2023)
In the currently developing digital era, the use of live streaming on the TikTok platform is becoming an increasingly popular marketing strategy. This research aims to determine the relationship between TikTok live streaming and increasing consumer trust and purchasing decisions. By utilizing a literature review as a research method, this research aims to explore information from previous research involving TikTok live streaming, consumer trust, and purchasing decisions. Previous research results show that TikTok live streaming plays an important role in shaping consumer trust through content authenticity and direct interaction. Product details displayed during live streaming and the quality of the streamer's presentation can influence purchasing decisions. TikTok Live Streaming is considered effective as a promotional medium that can build trust and increase consumer purchasing decisions.